THE EFFECTS OF OBESITY IN THE BLOOD PRESSURE ELEVATION - Putra, Tryvanie R (Majority, 2015)
Abstract In accordance to National Health Research in 2007, hypertension is the third deadliest cause of death, next to stroke and tuberculosis, numbering in 6.8%. The national prevalence of hypertension itself among the population above 18 years is 31.7% (in calculation).The development of hypertension is influenced by many factors. Those factors are the lack of physical activity and obesity, smoking habits, stress, biological inheritance, and consumption of high fat diet, lack of fiber, high natrium, and low kalium.The research conducted in 1959 showed the direct relation of hypertension and overweightness; Framingham’s research also found the elevation in blood pressure in adolescence that diagnosed with overweight.The pathogenesis of obesity causing hypertension is a complex mechanism, because of the main cause itself is various, and highly connected on each other. Leptin, free fatty acid, insulin, and obstructive sleep apnea that is found elevated in obesity will cause the constriction of the blood vessel and activation of sympathetic nervous system. Resistance in insulin and endothelial dysfunction also resulting in vascular constriction of the blood vessel. Heightened activity of sympathetic nervous system of the kidney, insulin resistance, and hyperactivity of renin-angiotensin system are known to cause the reabsorption of natrium in the kidney itself also become elevated. All of those mentioned factors above are known to be the cause of hypertension. Keywords: hypertension, leptin ,obesity, obstruktive sleep apnea Abstrak Berdasarkan Riskesdas Nasional tahun 2007, hipertensi merupakan pola penyebab kematian semua umur ketiga, setelah stroke dan TB, dengan proporsi kematian sebesar 6,8%. Adapun prevalensi nasional hipertensi pada penduduk umur >18 tahun adalah sebesar 31,7% (berdasarkan perhitungan).Berkembangnya hipertensi sangat dipengaruhi oleh banyak faktor. Faktor-faktor tersebut antara lain kurangnya aktivitas fisik dan obesitas, kebiasaan merokok, keadaan stress, riwayat keluarga, dan kebiasaan mengkonsumsi makanan tinggi lemak hewani, kurangnya serat, tinggi natrium dan rendah kalium.Penelitian tahun 1959 menunjukkan adanya hubungan langsung antara hipertensi dengan berat badan yang berlebihan; penelitian Framingham juga menemukan adanya kenaikan tekanan darah pada dewasa muda yang mempunyai berat badan lebih.Patogenesis obesitas mengakibatkan hipertensi merupakan hal yang kompleks karena penyababnya multifaktor dan saling berhubungan. Leptin, asam lemak babas dan insulin serta obstruktive sleep apnea yang meningkat pada obesitas akan menyebabkan konstriksi dan aktifitas sistem saraf simpatis. Resistensi insulin dan disfungsional endothelial juga menyebabkan vasokonstriksi.Peningkatan aktifitas saraf simpatis ginjal, resistensi insulin dan hiperaktifitas sistem renin angiotensi menjadikan reabsorbsi natrium pada ginjal meninggi. Semua faktor diatas akan mengakibatkan terjadinya hipertensi. Kata kunci:hipertensi,leptin, obesitas, obstruktive sleep apnea